Desain Propeller Yamaha Saltwater Series II Menggunakan Metode Interpolasi - Muhammad Rifqi Zulfahmi; R Dimas Endro Witjonarko; Lely Pramesti (Politeknik Perkapalan Negeri Surabaya, 2023)
The challenge when using an outboard engine is that all parts used have been packaged bythe manufacturer, so if there are damaged parts such as a bent propeller, you must buy from anauthorized distributor. In areas that are far from reach, it takes a lot of time and money to get partsofficially. Therefore, a research was conducted as an alternative effort to develop manufacturingtechnology, especially propellers. So that people can choose several options regarding the productsused. To get the same performance and characteristics, manual measurements are taken. But bymeans of measurement alone is not enough to make the image similar to the original, it is necessaryto make improvements with the interpolation method as an approach in drawing the propeller bladeprofile. After the research this method is very effective in drawing the shape of the propeller profilethis is evidenced by the interpolation method the resulting shape looks smoother. In addition, severalother aspects were also measured for propeller similarity. The results of the measurements obtained ablade area value of 19800 mm², a rake angle of 22°, a skew angle of 40°, a root length of 150 mm anda root angle of 90°.